2014
DOI: 10.1007/978-3-319-01863-8_26
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Compression Strategy for Time Series Database Using GPU

Abstract: Nowadays, we can observe increasing interest in processing and exploration of time series. Growing volumes of data and needs of efficient processing pushed research in new directions. GPU devices combined with fast compression and decompression algorithms open new horizons for data intensive systems. In this paper we present improved cascaded compression mechanism for time series databases build on Big Table-like solution. We achieved extremely fast compression methods with good compression ratio.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 7 publications
0
17
0
Order By: Relevance
“…We have shown that finding the optimal compression plan by a dynamic data analysis may significantly improve results without sacrificing the decompression speed [16].…”
Section: Lightweight Compression Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…We have shown that finding the optimal compression plan by a dynamic data analysis may significantly improve results without sacrificing the decompression speed [16].…”
Section: Lightweight Compression Methodsmentioning
confidence: 98%
“…Their main purpose is to increase a data throughput by a reduction of a data volume. A detailed description of presented compression algorithms may be found in [6,22,4,15].…”
Section: Lightweight Compression Methodsmentioning
confidence: 99%
“…They developed a planner for cascading compression techniques, which decides on a suitable subset and order of available compression techniques. Przymus and Kaczmarski focused on compression for time-series databases on the GPU [50]. Andrzejewski and Wrembel discussed compression of bitmap indexes on the GPU [4].…”
Section: Potential Optimizations For Gdbmssmentioning
confidence: 99%
“…It may diminish the gain of the acceleration credited to GPU. In our previous works we showed that this data transfer cost can be reduced using lightweight compression methods [12,13,14]. However, this does not solve all the problems since not all tasks may be effectively faster on GPU.…”
Section: Introductionmentioning
confidence: 99%
“…Also specialized systems, for example time series databases, may benefit from parallel execution of numerical computations like interpolation, approximation, pattern matching or compression [7,1,12,5,13,14].…”
Section: Introductionmentioning
confidence: 99%